The presence of depression and anxiety do not distinguish between functional jerks and cortical myoclonus. (December 2017) - Zutt, R.; Gelauff, J.M.; Smit, M.; van Zijl, J.C.; Stone, J.; Tijssen, M.A.J.
Abstract: Introduction: Functional movement disorders are accompanied by a high occurrence of psychopathology and cause serious impairments in quality of life. However, little is known about this in patients with functional jerks and no comparison has been made between patients with functional jerks and organic myoclonus. This case control study compares the occurrence of depression, anxiety and quality of life (HR-QoL) in patients with functional jerks and cortical myoclonus. Methods: Patients with functional jerks and cortical myoclonus, consecutively recruited, were compared on self-rated anxiety (Beck Anxiety Inventory), depression (Beck Depression Inventory), health-related quality of life (RAND-36), and myoclonus severity (UMRS and CGI-S rating scales). Results: Sixteen patients with functional jerks and 23 with cortical myoclonus were evaluated. There was no significant difference in depression (44% vs. 43%) or anxiety (44% vs. 47%) scores between groups. The HR-QoL was similarly impaired except that functional jerks patients reported significantly more pain (p < 0.05). Only in the functional jerks group myoclonus severity correlated with depression and anxiety. Conclusion: Depression and anxiety scores are high and do not discriminate between functional jerks and cortical myoclonus. Quality of life was equally impaired in both sub-groups, but pain was significantly worse in patients with functional jerks. Highlights: High rates of depression and anxiety in FJ and CM. Depression and anxiety do not discriminate between FJ and CM. Health related quality of life is equally impaired in FJ and CM. FJ patients experience significantly more pain than CM patients.